Geomorphia: Did the Earth Move For You? Mobile Capital as Geomorphic Agent. - Faucher, Kane (Reconstruction: Studies in Contemporary Culture, 2013)
The article attempts to provide a different insight for exploring the issue of mobile capital in both the domain of earth-moving technologies and mobile labour. It explores the transition from traditional capitalist strategies of accumulation to those indexed on acceleration under a wider framework of what may be called modular capitalism. It focuses on earth moving technologies and the stage of modular capitalism and data extraction practices to accelerate production and regulate behaviors.